2002
DOI: 10.4049/jimmunol.168.12.6494
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Proliferative Response of Vα24 NKT Cells from Cancer Patients Against α-Galactosylceramide

Abstract: Human invariant Vα24+ NKT cells are a relatively new subpopulation of lymphocytes. It has been reported that Vα24 NKT cells are significantly involved in some human diseases. We have evaluated the number and function of Vα24 NKT cells in both healthy volunteers and cancer patients. In this study we found that Vα24 NKT cells in unfractionated PBMCs obtained from cancer patients did not respond efficiently to α-galactosylceramide (α-GalCer) in vitro. Thus, their proportion after stimulation with α-GalCer was sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 25 publications
10
101
3
Order By: Relevance
“…We have confirmed with considerably larger subject numbers in this study that the percentage of Va24 þ NKT cells in cancer patients does not significantly differ to that in healthy donors when all cancer types are considered collectively (Yanagisawa et al, 2002). Our data also support previous reports that NKT cell numbers are significantly reduced in patients with melanoma (Kawano et al, 1999a); however, in contrast to Motohashi et al (2002) decreased frequency and absolute number of NKT cells was not seen in lung cancer patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have confirmed with considerably larger subject numbers in this study that the percentage of Va24 þ NKT cells in cancer patients does not significantly differ to that in healthy donors when all cancer types are considered collectively (Yanagisawa et al, 2002). Our data also support previous reports that NKT cell numbers are significantly reduced in patients with melanoma (Kawano et al, 1999a); however, in contrast to Motohashi et al (2002) decreased frequency and absolute number of NKT cells was not seen in lung cancer patients.…”
Section: Discussionsupporting
confidence: 92%
“…Significant reductions in PB NKT cell numbers have been reported in patients with melanoma, prostate cancer and lung cancer (Kawano et al, 1999a;Tahir et al, 2001;Motohashi et al, 2002), however in other studies the numbers of NKT cells in advanced cancer patients are comparable to those in healthy individuals (Yanagisawa et al, 2002). Variations in NKT cell function have also been described.…”
mentioning
confidence: 97%
“…13,[41][42][43][44] We reported that the number of Va24 1 NKT cells among PBMCs is reduced in patients with lung cancer but their ability to produce IFN-c remains intact. 13 In patients with advanced gastrointestinal cancers, the in vitro expansion of Va24 1 NKT cells was impaired, although it recovered partially by coculture with G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NKT cells are reduced in advanced prostate cancer patients and have decreased proliferation and cytokine production compared with healthy controls. 36 Subsequent reports showed decreased proliferative invariant NKT cell responses from patients with a variety of neoplastic diseases 102 and showed that freshly isolated invariant NKT from patients with specifically progressive multiple myeloma had a marked decrease in IFN-␥ production. 103 Livers from patients with metastatic disesase show a reduced frequency of V␣24ϩ NKT cells compared with healthy controls.…”
Section: Role In Tumor Surveillancementioning
confidence: 99%